Pengaruh APS, Pengangguran, PDRB, dan Jumlah Penduduk Terhadap Tingkat Kemiskinan Kota Surabaya - Salsafadhila, Safina; Cahyono, Hendry (Universitas Negeri Surabaya, 2023)
The city of Surabaya is metropolitan city and is also the 2nd largest city in Indonesia after the city of Jakarta. The city of Surabaya is xperiencing continuous development in aspect, education, health, infrastructure, and so on. This study aims to determine the effect of APS, Unemployment, GDP, and population in the City of Surabaya. The method used in this research is quantitative method. The analysis technique used is Multiple Linear Analysis. The results of this study resulted that APS, GDP, and population had no effect on Poverty in the City of Surabaya, while Unemployment had an effect on Poverty in the City of Surabaya.